Respuesta :

Answer:

Step-by-step explanation:

log(5) + log(X) = log(5x)

log( 5x) - log(x - 6) = log (5x/(x - 6))

antilog(log(5x/(x - 6)) = antilog(1)

5x / (x - 6) = 10                                        multiply both sides by x - 6

5x  = 10(x - 6)                                          remove the brackets

5x = 10x - 60                                          Subtract 10 x from both sides

5x - 10x = - 60

-5x = - 60                                               Divide by 5

x = 12